UJI PENINGKATAN MUTU BATUBARA PERINGKAT RENDAH SUMATERA SELATAN - Hartiniati Hartiniati (Jurnal Energi dan Lingkungan (Enerlink), 2011)
A study of coal upgrading by way of evaporative method using coal from SouthSumatra is conducted. Preliminary inestigation on Upgrading of Brown Coal(UBC) process using Central and South Banko coals suggests that the processcan be applied to both coals (called S-BK and C-BK) without any operationalproblem. It produces high quality-stable coals in the briquette form with a calorificvalue of more than 6,500kcal/kg. Moreover, its spontaneous combustioncharacteristic is also suppressed comparing to that conventional drying method.This is due to the addition of aspal (heavy oil) in the solution of kerosene, wherethe aspal then soaked in the micropore of to prevent reabsorption of water whenput in the air.Kata Kunci: upgrading brown coal, Banko coal, briket batubara, spontaneouscombustion